2019
DOI: 10.1093/biostatistics/kxz017
|View full text |Cite
|
Sign up to set email alerts
|

On models for the estimation of the excess mortality hazard in case of insufficiently stratified life tables

Abstract: In cancer epidemiology using population-based data, regression models for the excess mortality hazard is a useful method to estimate cancer survival and to describe the association between prognosis factors and excess mortality. This method requires expected mortality rates from general population life tables: each cancer patient is assigned an expected (background) mortality rate obtained from the life tables, typically at least according to their age and sex, from the population they belong to. However, thos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 23 publications
(46 reference statements)
0
35
0
Order By: Relevance
“…However, in the case of lung cancer, patients are more likely to smoke and have higher risk of mortality than the general population. Studies showed that lung cancer mortality hazard was overestimated, and consequently, lung cancer net survival was underestimated when not using smoking-specific life-tables 33,34 . In New Zealand, data on smoking status is collected every 7 years during population census.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the case of lung cancer, patients are more likely to smoke and have higher risk of mortality than the general population. Studies showed that lung cancer mortality hazard was overestimated, and consequently, lung cancer net survival was underestimated when not using smoking-specific life-tables 33,34 . In New Zealand, data on smoking status is collected every 7 years during population census.…”
Section: Discussionmentioning
confidence: 99%
“…However, this information was unavailable at population level. Consequently, the estimation of excess mortality hazards may be overestimated, and therefore our net survival estimates underestimated 64 .…”
Section: Discussionmentioning
confidence: 97%
“…Causal interpretation is only appropriate when lifetables are sufficiently stratified, but in principle lifetables can be constructed for any number of factors. To deal with this issue and consider other risk factors that are not always available on a population level, adjustments at the expected mortality rates have been suggested (Bower et al., 2017; Ellis et al., 2014; Rubio et al., 2019). Finally, we have assumed no intermediate confounders, that is no mediator–outcome confounder affected by the exposure (cross‐world independence assumption).…”
Section: Discussionmentioning
confidence: 99%
“…If the variables of the lifetables are insufficient then this assumption is violated. Various methods have been suggested to incorporate factors that are not available on population level (Bower et al., 2017; Ellis, Coleman, & Rachet, 2014; Rubio, Rachet, Giorgi, Maringe, & Belot, 2019).…”
Section: Exploring the Effect Of A Mediatormentioning
confidence: 99%